Sustainable Stocks and the Russian War on Ukraine - An Event Study in Europe - Andreas Kick; Horst Rottmann (Center for Economic Studies and ifo Institute (CESifo), 2022)
The popularity of sustainable investments is unbroken and attracts investors and researchers alike. Modelling the properties of such 'green' firms, Pástor, Stambaugh, and Taylor 2021 consider a hedge against climate risks in their theoretical model. Likewise, it could be assumed that companies with high social scores might offer a protection against related events. On February 24, 2022 with the Russian invasion on Ukraine one of the biggest events imaginable came to pass. Using standard event study methodology we analyse if and how Refinitiv's ESG-ratings, as well as the CO2 intensity, influence the cumulative abnormal returns during different event windows. We find that the abnormal returns of companies with high ecological scores are positively influenced in the pre and post-event window. However the effects are of no economical relevance. Therefore our results do not fully support the hypothesis of an 'ESG-hedge' against such an extreme event. If such an effect exists, it was superimposed by other properties accounting for stability and defensiveness.
Keywords: G11; G14; M14; 330; abnormal returns; war; Ukraine; ESG